Odorous compounds sources and transport from a swine deep-pit finishing operation: A case study. (1st March 2019) - Trabue, Steven; Scoggin, Kenwood; Tyndall, John; Sauer, Thomas; Hernandez-Ramirez, Guillermo; Pfeiffer, Richard; Hatfield, Jerry
Abstract: Odor emissions from swine finishing operations are an air quality issue that affects residents at the local level. A study was conducted at a commercial swine deep-pit finishing operation in central Iowa to monitor odorous compounds emitted and transported offsite. Gaseous compounds were sampled using either sorbent tubes or canisters with GC/MS analysis, and particulates matter (PM10 ) were sampled with high volume samplers and thermally extracted onto sorbent tubes for GC/MS analysis. Major odorous chemical classes detected at the swine facility included volatile sulfur compounds (VSC), volatile fatty acids (VFA), phenol and indole compounds. Manure storage was the main source of odorous compounds of which hydrogen sulfide (H2 S), methanethiol, 4-methylphenol, and 3-methylindole were key offenders. Only H2 S and 4-methylphenol were detected above odor threshold values (OTV) at all locations around the facility and both 4-methylphenol and 3-methylindole were detected above their OTV 1.5 km downwind from the swine facility. Odorous compounds generated during agitation and pumping of the deep pits was mainly H2 S. Odorants were mainly transported in the gas phase with less than 0.1% being associated with PM10 . Odor mitigation efforts should focus on gaseous compounds emitted from deep-pits and especially during manure agitation and deep-pit pumping. Graphical abstract: Image 1 Highlights: Odor from swine operations originates predominately in manure storage areas. Most odor is transported in the gas phase with less than 0.1% associated with dust. Downwind transport of odor is mainly associated with indole and phenol compounds. Hydrogen sulfide is the most significant odorant generated during agitation of manure deep-pts.